No evidence for consistent long‐term growth stimulation of 13 tropical tree species: results from tree‐ring analysis. (19th June 2015) - Groenendijk, Peter; van der Sleen, Peter; Vlam, Mart; Bunyavejchewin, Sarayudh; Bongers, Frans; Zuidema, Pieter A.
Abstract The important role of tropical forests in the global carbon cycle makes it imperative to assess changes in their carbon dynamics for accurate projections of future climate–vegetation feedbacks. Forest monitoring studies conducted over the past decades have found evidence for both increasing and decreasing growth rates of tropical forest trees. The limited duration of these studies restrained analyses to decadal scales, and it is still unclear whether growth changes occurred over longer time scales, as would be expected if CO2‐fertilization stimulated tree growth. Furthermore, studies have so far dealt with changes in biomass gain at forest‐stand level, but insights into species‐specific growth changes – that ultimately determine community‐level responses – are lacking. Here, we analyse species‐specific growth changes on a centennial scale, using growth data from tree‐ring analysis for 13 tree species ( 1300 trees), from three sites distributed across the tropics. We used an established (regional curve standardization) and a new (size‐class isolation) growth‐trend detection method and explicitly assessed the influence of biases on the trend detection. In addition, we assessed whether aggregated trends were present within and across study sites. We found evidence for decreasing growth rates over time for 8–10 species, whereas increases were noted for two species and one showed no trend. Additionally, we found evidence for weak aggregated growth decreases at the site in Thailand and when analysing all sites simultaneously. The observed growth reductions suggest deteriorating growth conditions, perhaps due to warming. However, other causes cannot be excluded, such as recovery from large‐scale disturbances or changing forest dynamics. Our findings contrast growth patterns that would be expected if elevated CO2 would stimulate tree growth. These results suggest that commonly assumed growth increases of tropical forests may not occur, which could lead to erroneous predictions of carbon dynamics of tropical forest under climate change.